1998
DOI: 10.1080/00224549809600354
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Weil-Being Among the Older Metropolitan and Nonmetropolitan Populations in the United States

Abstract: The relationships were examined between selected sociodemographic variables and perceptions of well-being among residents 60 years and older of metropolitan and nonmetropolitan areas in the United States. Multiple regression models were used in analyzing data from the 1982-1991 NORC General Social Survey. Such sociodemographic variables as gender, race, marital status, education, financial status, place of residence, religious membership, and religious attendance were independent variables. A composite score o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The fact that people go outside more, to walk and to participate in activities makes the area feel more accessible. This explanation is consistent with findings from previous studies (Chiu et al, 2005; Evans, 2009; Fokkema et al, 1996), which have indicated a greater quantity of coincidental meetings outside the home and a higher sense of well-being in the countryside compared with older adults in large urban areas (Mookherjee, 1998). Thus, older adults in rural settlements in a peripheral region maintain more social relations than those who live in central big urban environments.…”
Section: Discussionsupporting
confidence: 93%
“…The fact that people go outside more, to walk and to participate in activities makes the area feel more accessible. This explanation is consistent with findings from previous studies (Chiu et al, 2005; Evans, 2009; Fokkema et al, 1996), which have indicated a greater quantity of coincidental meetings outside the home and a higher sense of well-being in the countryside compared with older adults in large urban areas (Mookherjee, 1998). Thus, older adults in rural settlements in a peripheral region maintain more social relations than those who live in central big urban environments.…”
Section: Discussionsupporting
confidence: 93%
“…It is not surprising that perceptions of life and work quality reflect these racially distinct experiences. Over the past 30 years, longitudinal analyses of the General Social Survey (GSS) repeatedly find that blacks are less satisfied than whites along a continuum of quality-of-life measures (Hughes and Thomas 1998;Mookherjee 1998;Tuch and Martin 1991). Similar patterns hold for workplace satisfaction among black and white employees sharing the same occupation.…”
Section: Job Satisfaction Race and Gendermentioning
confidence: 94%
“…Religious organizations can function as both a formal and informal support system-or serve as a bridge between the two-through the development of intimate social interactions or "connections" (Sherr, Shields, King, & Curran, 2005). This is a unique and important association, as social connectedness has a substantial impact on an individual's well-being, particularly for the lives of older adults (Mookherjee, 1998). Overall, research in this area has found that developing and maintaining social relationships is associated with healthy aging (Karatas & Duyan, 2008).…”
Section: Social Connections and Well-beingmentioning
confidence: 97%